The Geopolitics of Public Memory: The Challenge and Promise of Transnational Comfort Women Activism. Issue 2 (3rd April 2022) - Nadesan, Majia; Kim, Linda
Abstract: Japan conscripted a disputed number of "comfort women" to sexually service their soldiers in occupied territories during World War II. In the aftermath of war, this apparatus was ignored by international diplomacy, and few survivors related their experiences as sex slaves. However, during the early 1990s, sexual crimes against women achieved international attention, emboldened by and emboldening silence breakers whose personal experiences were both affirmed and negated by competing global stakeholders. Activists seeking recognition of and reparations for crimes against survivors of Japan's comfort women system have since deployed memorials to contest Japan's position that comfort women were sex workers. These memorials materially instantiate the conflicted interpretations of the scope and severity of Japan's war crimes, whose undecidability signifies ruptures in the contemporary symbolic order of the United States, Japan, and South Korea alliance. This project examines how online audiences construct the meanings of the highly contested 2017 San Francisco memorial.